Effect of a High Fat and High Protein Diet on Exercise-Induced Skeletal Muscle Hypertrophy in Rats - Fujii, Takako; Sonou, Tomohiro; Nakai, Naoya; Okamura, Koji (International Journal of Nutrition, 2019)
The skeletal muscle mass varies by race. Dietary habits over generations are a factor that influences the skeletal muscle mass, as well as genetic factors. Therefore, we investigated the effects of diets with different macronutrient contents on exercise-induced muscle hypertrophy in rats. Male 4-week-old Sprague–Dawley rats were randomly divided into three groups: a normal-diet (N), high-protein diet (HP) and high-fat diet (HF) group. The food intake was manipulated to gain comparable body weight across the three groups. All rats were performed a climbing exercise training for 8 weeks. The final body weight and weight of the liver, kidneys and adipose tissues did not significantly differ among the groups. The flexor hallucis longus was significantly higher in the HF group than in the HP group. The total lipid content in the muscle was significantly higher in the HF group than in the N group, while it did not differ significantly between the HF and HP groups. There were no marked differences in the water or protein content in the muscle among the groups. The plasma amino acid concentration was significantly or tended to be lower in the HP group than in the HF or N group, except for the branched-chain amino acid concentration, which tended to be higher after ingesting the HP diet than other diets. These findings suggest that consuming an HP diet is not likely to facilitate exercise-induced muscle hypertrophy, partly due to the plasma amino acid imbalance induced by habitual HP diet consumption.
Keywords: sports nutrition; skeletal muscle; high protein diet; high fat diet